The effect of neurostimulation applied to the left dorsolateral prefrontal cortex on post-stress adaptation as a function of depressive brooding - De Witte, Sara; Baeken, Chris; Pulopulos, Matias M.; Josephy, Haeike; Schiettecatte, Johan; Anckaert, Ellen; De Raedt, Rudi; Vanderhasselt, Marie-Anne (Progress in neuro-psychopharmacology & biological psychiatry, 2020)
Depressive brooding following a stressful event predicts negative affect and neuroendocrine responses related to psychological stress. The dorsolateral prefrontal cortex (DLPFC) has been associated with the top-down regulation of thoughts and emotions, and abnormal neural activity within this region has been associated with increased psychological stress and ruminative thinking. The aim of this study was to investigate whether the modulation of the DLPFC could have beneficial effects on ruminative thoughts and the endocrine response following a self-relevant stressor. Using a sham-controlled within-subjects crossover-design, two sessions of intermittent theta-burst stimulation (iTBS) were administered over the left DLPFC to thirty-eight healthy-volunteers after they were confronted with a social-evaluative stressor, the Trier Social Stress Test. To assess stress recovery, momentary rumination was measured before and after a resting period subsequent to the encounter with the stressor. In addition, cortisol levels were measured between and after the two iTBS sessions that were applied during the stress recovery phase. Overall, iTBS did not significantly influence ruminative thinking and cortisol secretion during the stress recovery phase. However, taking into account participants ruminative tendencies, our results revealed that for participants with higher levels of brooding ruminative thinking remained stable after iTBS, whereas in the sham condition there was a marginal significant increase in ruminative thinking. Moreover, only after iTBS, there was a significant reduction in cortisol secretion (i.e. a faster return to baseline as compared to sham) for high brooders during the recovery from the stressor. These results show that the prefrontal cortex plays a role in stress recovery mechanisms in individuals who are more vulnerable for psychopathology. •We investigated the effect of iTBS on cortisol recovery and ruminative thinking after stress.•We investigated the role of depressive brooding in the effects of iTBS on cortisol and ruminative thinking.•After active iTBS, there was a significant reduction in cortisol secretion during the stress recovery for high brooders.•In the sham condition, there was a marginal increase in ruminative thinking during the stress recovery for high brooders.